Effect of using the WeChat platform on the perioperative health education of parents of children who underwent transthoracic device closure of VSDs - Qi-Liang Zhang (Journal of Cardiothoracic Surgery, 2020)
Abstract Objective To explore the effects of using the WeChat platform on the perioperative health education of parents of children who underwent transthoracic device closure of ventricular septal defects (VSDs). Methods Participants were divided into a WeChat group and a leaflet group. Responses to relevant questionnaires and clinical data were recorded and analyzed. Results Before the operation, the scores of the Caretaker Knowledge Questionnaire in the WeChat group were significantly higher than those in the leaflet group. The scores of PSQ-18 in the WeChat group were significantly higher than those in the leaflet group. All the children in the WeChat group were followed up 1 month after discharge, while four children in the leaflet group were lost to follow-up. The rate of attrition in the leaflet group was significantly higher than that in the WeChat group. For the postoperative complications, there was no significant difference between the two groups. Conclusion Perioperative health education for parents of children who undergo transthoracic device closure of VSDs through the WeChat platform can effectively enhance parents’ knowledge of care, improve parent satisfaction, which is an effective method to ensure convenient operation and reduce loss to follow-up.